Research trends in pediatric splenic trauma in Brazil: how much has changed in the last two decades? - Luiza Telles; Ayla Gerk; Ana Maria Diniz; Madeleine Carroll; Sarah Lopes; Ana Kim; Brenda Feres; Anna Fontes; Roseanne Ferreira; Joaquim Bustorff-Silva; David P. Mooney (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: Research in high-income countries has extensively documented the non-operative management of spleen injuries in children, resulting in low splenectomy rates (5%). However, there is a lack of literature on this topic in low- and-middle-income countries (LMICs), including Brazil. This scoping review analyzed pediatric spleen trauma research trends in Brazil and the United States of America (USA). Methods: Search strategy was conducted across five databases, considering articles published in English or Portuguese from January 1968 to 2023 that reported spleen injury in patients younger than 18 years old in Brazil or the USA. Two pairs of independent reviewers screened the title and the abstract, followed by a full-text review. Results: The total of 7,150 studies was identified, of which 295 were eligible for data extraction. Most papers (98.64%, 301) originated from the USA, while only 1.36% (4) were from Brazil. In addition, 46.44% (137) articles reported intrabdominal injury, including splenic trauma, 16.27% (48) liver and spleen injury, and 37.29% (110) reported isolated spleen injury. The operative rate for spleen injury was 11.33% in American studies (40,812/359,926) compared to 98.57% (137/139) in Brazilian studies. Conclusions: Brazil contributed only with four studies on pediatric splenic trauma over two decades. Future studies should explore the incidence and management of splenic trauma in LMICs.